2019
DOI: 10.3390/s19163524
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Performance of Type I Fibre Bragg Grating Strain Sensors

Abstract: Although fibre Bragg gratings (FBGs) offer obvious potential for use in high-density, high-strain sensing applications, the adoption of this technology in the historically conservative aerospace industry has been slow. There are several contributing factors, one of which is variability in the reported performance of these sensors in harsh and fatigue prone environments. This paper reports on a comparative evaluation of the fatigue performance of FBG sensors written according to the same specifications using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…FOSs do not experience strain drift or fatigue damage under normal operating conditions, as specified in [1]. Previous testing by the authors showed that draw tower gratings, which are similar to AGF, survived an incremental constant amplitude loading sequence (Table 1) accumulating 3 million applied load cycles, with failure eventually occurring at a strain of 23,000 µƐ [2]. It was previously mentioned that FOSs provide significant reductions in weight and complexity of installation relative to FSGs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FOSs do not experience strain drift or fatigue damage under normal operating conditions, as specified in [1]. Previous testing by the authors showed that draw tower gratings, which are similar to AGF, survived an incremental constant amplitude loading sequence (Table 1) accumulating 3 million applied load cycles, with failure eventually occurring at a strain of 23,000 µƐ [2]. It was previously mentioned that FOSs provide significant reductions in weight and complexity of installation relative to FSGs.…”
Section: Resultsmentioning
confidence: 99%
“…A 3.25 m long AGF sensor with 2024 sensing points was selected to provide strain measurements every 1.6 mm with a notional strain measurement accuracy of ±1με. This type of FOS is mechanically robust with a 5% (50,000 𝜇𝜇𝜇𝜇) tensile failure strain [1] and exceptional fatigue resistance [2].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The dynamic range of this rig was designed to induce tensile strains in an optical fibre of up to 36,000 µε at a fixed 100 Hz cyclic loading frequency [20]. [20], with the FBG mounted between the moving part and the stable part (labelled).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Recently, many researchers have been using FBGs for crack detection [12][13][14][15] and SHM [16,17] because of their good linearity and resistance to harsh environments [18]. Even their fatigue performance is superior to the alternative electrical resistance SGs [19]. It must be noted that this is related to the sensor itself and not to a sensor that is glued to a structure.…”
Section: Introductionmentioning
confidence: 99%